(untitled) (De Legibus - Law Journal, 2024)
This work aims to describe the main methods of interpreting the rules that apply VAT exemptions and reduced rates and to outline the difference in treatment of the teleological element, provided by the European Court of Justice, when applying such interpretations standards and when employing the principle of tax avoidance.